Sleep health in Swiss elite athletes. An online survey - Albrecht Vorster; Michael J. Schmid; Daniel Erlacher (Bern Open Publishing, 2024)
Introduction There is no doubt that high-quality sleep is essential for athletes' health, regeneration, and performance (Vorster et al., 2022). Unfortunately, sleep problems are as widespread in professional sports as they are in the rest of the population: about 11% of athletes have problems falling asleep and staying asleep, 20% have serious problems with sleep during competition periods, 30% are taking sleeping pills during the season, 10% show symptoms of obstructive sleep apnoea, 5% show symptoms of restless leg syndrome, and 15% report anxiety dreams before competitions (Gupta et al., 2017; Tuomilehto et al., 2017; Walsh et al., 2021). Comparative work that systematically analyses and compares sleep problems across sports remains scarce, so these figures should be viewed with caution. Especially for Swiss elite athletes' representative numbers about the main sleep disorders are missing. The aim of the study is therefore to examine the status of sleep health among elite Swiss athletes. Methods An online questionnaire was sent to all Swiss elite athletes. Over 1,000 athletes (data collection is still running) filled out the questionnaire on various symptoms of sleep problems. The questionnaire included at least one item to screen for the six main categories of sleep disorders. These items were taken from different validated sleep questionnaires (e.g., PSQI, ASBQ, SDS). Results The prevalence of symptoms associated with sleep disorders of the six main categories: 'insomnias' 'sleep-related breathing disorders', 'central disorders of hypersomnolence', 'circadian rhythm sleep-wake disorders', 'parasomnias', 'sleep-related movement disorders' will be presented. Discussion/Conclusion This online survey will provide representative data on the prevalence of sleep problems in Swiss elite athletes. The dataset will provide novel insides into the distribution of certain sleep problems over the various sports in Switzerland. Sleep problems in athletes certainly need to be taken seriously and treated. They are often not just concomitants of other illnesses and problems. Therefore, important practical implications will be discussed. References Gupta, L., Morgan, K., & Gilchrist, S. (2017). Does elite sport degrade sleep quality? A systematic review. Sports Medicine, 47(7), 1317-1333. https://doi.org/10.1007/s40279-016-0650-6 Halson, S. L. (2013). Sleep and the elite athlete. Sports Science Exchange, 26(113), 1-4. Tuomilehto, H., Vuorinen, V.-P., Penttilä, E., Kivimäki, M., Vuorenmaa, M., Venojärvi, M., Airaksinen, O., & Pihlajamäki, J. (2017). Sleep of professional athletes: Underexploited potential to improve health and performance. Journal of Sports Sciences, 35(7), 704-710. https://doi.org/10.1080/02640414.2016.1184300 Vorster, A., Erlacher, D., Barrazoni, F., Hossner, E.-J., & Bassetti, C. (2022). Schlafprobleme im Leistungssport [Sleep problems in competitive sport]. Swiss Medical Forum ‒ Schweizerisches Medizin-Forum, 22, 198-203. https://doi.org/10.4414/smf.2022.08941 Walsh, N. P., Halson, S. L., Sargent, C., Roach, G. D., Nédélec, M., Gupta, L., Leeder, J., Fullagar, H. H., Coutts, A. J., Edwards, B. J., Pullinger, S. A., Robertson, C. M., Burniston, J. G., Lastella, M., Le Meur, Y., Hausswirth, C., Bender, A. M., Grandner, M. A., & Samuels, C. H. (2021). Sleep and the athlete: Narrative review and 2021 expert consensus recommendations. British Journal of Sports Medicine, 55(7), 356-368. https://doi.org/10.1136/bjsports-2020-102025